Didactic Design of Cube Nets based on Ethnomathematics of Engklek Game in Elementary School : An Educational Innovation - Andika Arisetyawan; Rika Asterina Ariadi; Irfan Fauzi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
The purpose of this research is to develop a didactic design for cube nets based on the ethnomathematics of the Engklek game in elementary schools. This study uses a design research approach using the Didactical Design Research (DDR) method. The participants in this research are 5th and 6th grade students at an elementary school in Serang-Banten. The research goes through three stages: 1) prospective analysis, 2) metapedadidactic analysis, and 3) retrospective analysis. Data collection techniques included tests, observations, interviews, and documentation. Data analysis techniques employed qualitative descriptive analysis based on Miles & Huberman's data triangulation model. The results of this research show that: 1) In the retrospective stage, obstacles such as conceptual errors, principle errors, and verbal errors were identified, which became the basis for creating the hypothetical didactic design, 2) In the metapedadidactic stage, the initial didactic design was developed by integrating the cultural elements of the Engklek game and resulted in a new 2-2-2 pattern, and 3) In the retrospective analysis, the revised didactic design based on the ethnomathematics of the Engklek game with the new 2-2-2 pattern can be used to teach the concept of cube nets in mathematics education. This research aims to develop a meaningful didactic design by incorporating local cultural contexts into mathematics learning in elementary schools. This research has significant implications for education, especially in improving the quality of mathematics learning with didactic designs that utilize cultural context in teaching materials.